2014
DOI: 10.1007/s13312-014-0550-5
|View full text |Cite
|
Sign up to set email alerts
|

Wiskott-Aldrich syndrome with macrothrombocytopenia

Abstract: This is a need for multidisciplinary assessment of patients with congenital or early infantile thrombocytopenia, including testing for mutations of the WAS gene in all unexplained cases even in the absence of characteristic microthrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
6
0
3
Order By: Relevance
“…increased platelet-derived micro-particles in WAS patients. 11 When compared to the previous studies which reported patients with normal MPV, 6,7,9,11 our patient had a mutation in the same exon reported by Skoric, et al, 9 but a different exon compared to the other 2 reports (exons 7, 9). 6,7 Thus the WAS diagnosis should consider even when patients have normal MPV, and there are no genotype-phenotype correlation.…”
Section: Report Of Casesupporting
confidence: 48%
See 1 more Smart Citation
“…increased platelet-derived micro-particles in WAS patients. 11 When compared to the previous studies which reported patients with normal MPV, 6,7,9,11 our patient had a mutation in the same exon reported by Skoric, et al, 9 but a different exon compared to the other 2 reports (exons 7, 9). 6,7 Thus the WAS diagnosis should consider even when patients have normal MPV, and there are no genotype-phenotype correlation.…”
Section: Report Of Casesupporting
confidence: 48%
“…Although micro-thrombocytopenia is one of the hallmarks of WAS, previous studies reported that XLT 6 and classic WAS 7 patients could have normal-sized or even giant-sized platelets. 9 The current theory regarding the mechanism of thrombocytopenia in WAS patients is explained by increased destruction of platelets in the spleen. 10 However, the mechanism of micro-thrombocytopenia in WAS remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is not always the case that patients with WAS have small platelets. Cases of WAS have been described with normal ( 13 , 14 ) or even increased ( 15 ) MPV. Furthermore, platelet size in one WAS patient was reported to vary over time with the dose of immunoglobulin replacement ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, macroplaquetas foram observadas em 2 pacientes (11,1%). Skoric et al (2014) (SULLIVAN et al, 1994;OCHS et al, 2006;AMARINTHNUKROWH et al, 2012). As hemorragias mais frequentes foram petéquias, sangramento intestinal e urinário.…”
Section: Resultsunclassified
“…Até o momento, já foram descritos 8 hotspots no gene WAS, que foram definidos como mutações idênticas ou missense em mesmo ou aumentado. É importante ressaltar que a ausência de microplaquetas não descarta o diagnóstico(PATEL et al, 2011;SKORIC et al, 2014;YOONESSI et al, 2015).…”
unclassified